Mechanical properties and electrical conductivity performance of ECAP processed AA2024 alloy - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2019)
This paper presents an experimental examination of AA2024 aluminium alloy through Equal Channel Angular Pressing (ECAP), annealing, and ECAPed plus aging applications. The aim of this study is to compare and observe the effects of the a forecited processes in terms of hardness and electrical conductivity. ECAP is one of the frequently used methods for Severe Plastic Deformation (SPD). SPD give rises to obtain stronger mechanical properties of materials as an improvement technique in material science. Four AA2024 specimens are prepared. One is as received sample, second is annealed AA2024, third one is ECAP processed and the last one is ECAP and then aging processed form. Hardness measurement is done as mechanical properties investigation. In addition, microstructure behaviour with SEM is studied. Once again, electrical conductivity of all four specimens are examined. All parameters are compared with each other. After annealing process the hardness of AA2024 is reduced according to as received form. ECAP increased the hardness, despite this, the highest hardness value is observed on ECAPed plus aging processed sample. The electrical conductivity of AA2024 is increased after annealing process according to as received form. However, it reduced after ECAPed plus aging process. Nevertheless, ECAPed sample gained more conductivity and has the least resistivity.
Keywords: ECAP; AA2024; Electrical Conductivity; SEM; TEXTURE DEVELOPMENT; 2024 AL; STRENGTH